Rheological Behavior of Zirconia Added Alumina Mixture - Norazlini Abd Aziz, Siti; Saiful Sarhan Wan Saidi, Wan; Azlina Abu Bakar, Mimi; Hussain Ismail, Muhammad (International Journal of Engineering and Technology, 2018)
Zirconia and alumina are one of the materials that is widely used in medical industry. Zirconia Toughened Alumina (ZTA) have great Â Â Â properties to be apply in the ceramic injection molding such as have high hardness and high strength. The powder used in this research are alumina and zirconia while the binder to be used in this research is using 100% single based binder of palm stearin (PS). Behavior of zirconia blended alumina was investigated by rheological testing at temperature 55Â°C. Two formulations were used which is 60% (alumina/zirconia) plus 40% PS and 64% (alumina/zirconia) plus 36% PS. The ratio of alumina and zirconia used in this research is fixed at (85:15) for both samples. Four basic process involved which is mixing process, injection molding, thermal debinding and sinteringÂ Â Â Â process has been implemented to complete ceramic injection molding (CIM). Sample were performed the thermal debinding at a heating rate 0.5Â°C/min up to 700Â°C and sintering at heating rate 3Â°C/min for temperature 1400Â°C and 1600Â°C. The hardness was tested using Rockwell hardness test for both AZ60 and AZ64 sample. Highest hardness was obtained from the sample AZ64 at the temperature 1600 Â°C which is 109HRR compare to the 1400Â°C that achieved 95.3HRR.Â Â